2006
DOI: 10.4049/jimmunol.176.8.4616
|View full text |Cite
|
Sign up to set email alerts
|

Selective Requirement of p38α MAPK in Cytokine-Dependent, but Not Antigen Receptor-Dependent, Th1 Responses

Abstract: The role of the p38 MAPK pathway in Th1 development has been controversial, because indirect manipulations of either upstream p38 activators or modifiers of p38 activity have had variable effects on IFN-γ production in CD4+ T cells. Uncertainties regarding the specificity of pharmacologic inhibition or p38 dominant negative mutants diminish the strength of conclusions about the role of the p38α isoform in Th1 development. Also, the effects of some upstream p38 activators, such as MAPK kinase 3, on Th1 developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 30 publications
3
38
1
Order By: Relevance
“…T cell-intrinsic p38 activity has been regarded as crucial for Th1 immune responses, a notion supported by studies with Gadd45␤ Ϫ/Ϫ and Gadd45␥ Ϫ/Ϫ mice (11,12). However, this idea has been challenged by recent observations from chimeric mice expressing p38␣-deficient T cells, in which Th1 polarization is normal (8). Those findings, together with the present observations, suggest that the role of p38 in Th1 polarization is primarily at the level of the DC rather than the T cell.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…T cell-intrinsic p38 activity has been regarded as crucial for Th1 immune responses, a notion supported by studies with Gadd45␤ Ϫ/Ϫ and Gadd45␥ Ϫ/Ϫ mice (11,12). However, this idea has been challenged by recent observations from chimeric mice expressing p38␣-deficient T cells, in which Th1 polarization is normal (8). Those findings, together with the present observations, suggest that the role of p38 in Th1 polarization is primarily at the level of the DC rather than the T cell.…”
Section: Discussionmentioning
confidence: 75%
“…Although the p38 inhibitors SB203580 and SC-409 blocked cytokine-mediated IFN-␥ production by Th1 cells, they did not prevent the activation, differentiation, or proliferation of new Th1 cells (5). Recently generated p38␣ Ϫ/Ϫ T and B cells developed and proliferated normally (7), and p38␣-deficient CD4 ϩ T cells differentiated into Th1 effector cells in vitro and expressed normal levels of IFN-␥ when restimulated through the TCR (8), suggesting that T cell p38␣ is dispensable for Th1 development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that the affinity of NF-B for the murine Il4 promoter is too weak to be detected (22). In keeping with the requirements for cytokine-stimulated induction of IL-13 and IL-17 in Th2 and Th17 cells, respectively, in Th1 cells, IL-18 plus IL-12-induced IFN␥ production is NF-B and p38 dependent and NFAT independent (10,23,24).…”
Section: Upregulation Of Receptors For Il-1 Family Members and Mastermentioning
confidence: 86%
“…Other investigators reported that p38␣Ϫ/Ϫ ESCs were able to differentiate into myeloid-like cells, but that these cells failed to produce IL-6 in response to IL-1 stimulation, as opposed to cells derived from wild type cells (Allen et al, 2000). Similarly, p38␣ was not essential for lymphocyte development (Kim et al, 2005), but p38␣ Ϫ/Ϫ Th1 cells were defective in IFN-␥ secretion stimulated by IL-12/ IL-18 (Berenson et al, 2006). These studies demonstrate the potential of using p38␣ Ϫ/Ϫ ESCs as a genetically defined tool to study this enzyme in the regulation of ESC activities and to provide results that otherwise are not obtainable from studies using fully differentiated adult cells.…”
Section: Introductionmentioning
confidence: 84%